Potency of Local Wisdom Augmented Reality (AR) Media in Physics Learning: Bibliometric Analysis - Damarsha, Adrian Bagas; Utami, Putri Lintang; Rahmawati, Ratna; Lintangesukmanjaya, Rahmatta Thoriq; Hidayaatullah, Hasan Nuurul; Nisa', Khoirun (Studies in Philosophy of Science and Education, 2025)
The era of technology provides many modern developments and innovations. One of them is in the field of education such as learning media. Physics learning media widely uses Augmented Reality (AR). This study aims to analyze network visualization, AR visualization overlay, and AR local wisdom in physics learning research as well as the distribution of media, trends, and opportunities for AR research and AR local wisdom in physics learning research. The bibliometric research method uses two keywords in the Scopus database, namely AR and AR Local Wisdom. Based on the results of the network visualization study, AR is defined as 8 clusters, and AR local wisdom is defined as 12 clusters. The innovation obtained based on the study of overlay visualization of current topics related to AR research and AR Local Wisdom, both of which are in critical thinking, has found research improvements for 7 years. The Physics Conference Series Journal is the source that provides the most contributions. The trend of AR local wisdom related to android applications in batik learning and the implementation of AR local wisdom in physics courses has not been done much and needs to be done.